PKM Pelatihan Praktik Melukis Teknik Fresco Bagi Murid dan Guru Di Sekolah Dasar INPRES Unggulan BTN. Pemda Makassar - Muhammad Saleh Husain; Sofyan Salam; Aswar Aswar (Universitas Negeri Makassar, 2020)
Presentation of material on the learning process of art education theory and art education practicum, whose behavior is directed at the method of presenting aesthetic concepts, creativity and work, adjusted to the level of ability of the students themselves. The connection in this case is to avoid the passivity of students during the learning process of fine arts education, through the presentation of educational media applied by the teacher will be a motivation to think creatively to apply freedom of exploration and freedom to express feelings and create real work in creating works. works of art in accordance with the structured assignment of subject matter from the teacher. The trend towards increasing teaching of fine arts education will benefit from being presented to formal educational institutions in an academic manner that is implemented at BTN's Inpres Featured Primary School. The local government of Makassar, regarding the learning process which has an innovative direction, both in the form of a presentation of basic theories and the practice of working in fine arts is quite a lot marked through the form of a teaching process that provides space for creativity, exploration, learning to work in Fresco technique painting, which of course begins with drawing learning exercises. sketches applied to students and teachers of the Inpres Unggulan BTN Elementary School. Pemda Makassar, so that students will experience a change from not knowing to knowing, through growth in attitudes and growth in thinking increasingly creative and intelligent